Personality and the gender gap in political ambition. (1st February 2020) - Allen, Peter; Cutts, David
Abstract : In this article, we offer an analysis of the gender gap in political ambition that takes personality and other canonical predictors of levels of ambition into account simultaneously. We use original large- N survey data from Britain. We find that the gender gap in nascent ambition is robust to the inclusion of measures of personality alongside traditional socio-economic predictors of political ambition. Second, we find that increased extraversion is related to higher levels of nascent ambition, but only for women. Third, we find that personality does not drive any move from intending to run for office to actually doing so.